Hemdrup runestav - Skautrup, Peter (Kuml, 1951)
The Hemdrup rune-stave In the course of peat cutting in Næsborg bog (Slet riding, North Jutland) in 1949 a yew stick was discovered (fig. 1), and found to bear two rune inscriptions (figs. 4 and 5) as well as various carved figures (including dogs and the figure of a woman; figs. 3, 4, 5 and 6) and designs (including a triskele; fig. 7). The archaeological and runological evidence appears to date the Hemdrup stave to the period 900-1000 (perhaps 1050) AD. Of the two runic inscriptions, the one, which can be read uanÞikiba I f I iukati I ąsa I auaąuri, may be interpreted: "(This) turnstave is owned by F; Atte carved (the runes); Åse, Ave's (Or grandfather's) money (i.e. treasure)". The stick can be identified, both from this interpretation of the inscription and from its appearance and ornamentation as a cattle herd's stick, i.e. a throwing stick. Throwing sticks (of which a number of dialect names are known) of this type were used up to our own day by Danish herdboys when watching cattle (figs. 11-14). By throwing such a stick the cattle could be stopped or guided. A number of throwing sticks from modern times are described, decorated with carvings of various types, showing parallels in many details to the ornamentation of the Hemdrup stave. Peter Skautrup